APPLICATIONS FRONTPAGE IN DESIGNING A WEB SITE MARKETING DIVISION OF EDUCATION INSTITUTIONS IN INDONESIA BRANCH AMERICAN KEBON JERUK - Wiwiek Pujiningsih; Jalinas SKom MM Jalinas SKom MM (Jurnal Sistem Informasi, 2002)
Marketing Division in each company at the forefront in introducing products to thepublic and marketing these products. Media marketing can through print andelectronic media. Print media for example newspapers, brochures and pamphlets.Electronic media, through television and radio.We have a faster delivery of media and can be accessed by everyone, namely throughthe Internet media. Give through the Internet media can be done by making thehomepage. With a homepage we can make a company profile which contains aboutthe company itself and existing products in this company.Making this homepage using Microsoft Frontpage. With Microsoft Front Page, wecan make the design of the home page and automatically create an HTML Front Pagewill be his. Front Page With this we can also insert images that we've scanned so thatthe home page that we create can attract attention of society to access the home pageof our company.With the home page is expected that the community will be more megenal aboutcompany background and existing products so that people can choose the product thatfits their needs, especially in selecting a training program they want.